(untitled) (Medico Legal Update, 2025)
Blood grouping plays a crucial role in medical diagnostics, transfusion practices, and forensic investigations. Traditional methods for determining blood groups involve serological testing of blood samples, which, while accurate, require invasive procedures, trained personnel, and time. Researchers have recently explored non-invasive alternatives, among which biometric approaches such as fingerprint analysis have gained attention. The emerging field of fingerprint-based blood grouping presents a revolutionary, non-invasive alternative by leveraging the unique biochemical composition of fingerprint residues and the distinct patterns of epidermal ridges. This approach offers significant value by enabling rapid, cost-effective, and hygienic blood type determination, with profound benefits for enhancing emergency response efficiency, streamlining donor registration in blood banks, and advancing forensic investigations. The purpose of this comprehensive review is to synthesize current research and provide a detailed overview of the methodologies underpinning this technology. We examine the scientific basis for the correlation between fingerprint patterns and ABO/Rh blood groups, evaluate traditional chemical and spectroscopic techniques, and analyze the cutting-edge integration of artificial intelligence (AI) and deep learning models for automated classification. Furthermore, the review discusses the practical applications, advantages, and current limitations of the technology, concluding with an outlook on future directions for research and implementation. This paper underscores the transformative potential of fingerprint-based blood grouping as a viable and promising solution for modern medical and forensic challenges. However, further research with larger and more genetically diverse populations is required to validate and refine the predictive models. In conclusion, while fingerprint-based blood grouping cannot yet replace conventional methods, it offers a compelling supplementary tool for rapid, non-invasive blood group estimation.